Evaluation of the Occlusion Status of Coiled Intracranial Aneurysms with MR Angiography at 3T: Is Contrast Enhancement Necessary? - Sprengers, M.E.S. (AJNR Am J Neuroradiol, 2009)
BACKGROUND AND PURPOSE: MR angiography (MRA) is increasingly used as a noninvasive imaging technique for the follow-up of coiled intracranial aneurysms. However, the need for contrast enhancement has not yet been elucidated. We compared 3D time-of-flight MRA (TOF-MRA) and contrast-enhanced MRA (CE-MRA) at 3T with catheter angiography. MATERIALS AND METHODS: Sixty-seven patients with 72 aneurysms underwent TOF-MRA, CE-MRA, and catheter-angiography 6 months after coiling. Occlusion status on MRA was classified as adequate (complete and neck remnant) or incomplete by 2 independent observers. For TOF-MRA and CE-MRA, interobserver agreement, intermodality agreement, and correlation with angiography were assessed by κ statistics. RESULTS: Catheter-angiography revealed incomplete occlusion in 12 (17%) of the 69 aneurysms; 3 aneurysms were excluded due to MR imaging artifacts. Interobserver agreement was good for CE-MRA (κ = 0.77; 95% confidence interval [CI], 0.55–0.98) and very good for TOF-MRA (κ = 0.89; 95% CI, 0.75–1.00). Correlation of TOF-MRA and CE-MRA with angiography was good. The sensitivity of TOF-MRA and CE-MRA was 75% (95% CI, 43%–95%); the specificity of TOF-MRA was 98% (95% CI, 91%–100%) and of CE-MRA, 97% (95% CI, 88%–100%). All 5 incompletely occluded aneurysms, which were additionally treated, were correctly identified with both MRA techniques. Areas under the receiver operating characteristic curve for TOF-MRA and CE-MRA were 0.90 (95% CI, 0.79–1.00) and 0.91 (95% CI, 0.79–1.00). Intermodality agreement between TOF-MRA and CE-MRA was very good (κ = 0.83; 95% CI, 0.65–1.00), with full agreement in 66 (96%) of the 69 aneurysms. CONCLUSIONS: In this study, TOF-MRA and CE-MRA at 3T were equivalent in evaluating the occlusion status of intracranial aneurysms after coiling. Because TOF-MRA does not involve contrast administration, this method is preferred over CE-MRA.